Participatory monitoring for system of rice intensification – farmer field school program in West Malaysia: perception and influential factors - Agnese, Federica (2022)
Participatory monitoring (PM) has increasingly been adopted in Farmer Field School (FFS) approaches. However, one of the biggest challenges is data management, as it is often led by externals without farmers’ involvement. Therefore, this study aimed to investigate perceptions and identify influential factors that enable farmers' and master trainers’ participation in PM. It eventually aimed to propose a framework f or participation in PM using the System of Rice Intensification (SRI) – Farmer Field School program in West Malaysia. A qualitative case study research design was employed in which the population was selected through a purposeful sampling technique. Then, the data collection through semi-structured interviews occurred from October 2020 until April 2021 in three locations. The thematic analysis method was used for data analysis. The findings revealed that the farmers' and master trainers’ perception was favourable, particularly regarding the phase of data collection and the use of digital applications to monitor field-level results. Indeed, the use of WhatsApp improved decision-making of SRI related innovations. The influential factors that enable participation in monitoring SRI-FFS were identified in the extrinsic factor of characteristics, the intrinsic factors of perception, knowledge, and attitudes. The results indicate that perception and knowledge influenced positive attitudes. Furthermore, the results revealed that the indicators of commitment and trust strengthened the influential factor of attitudes by integrating social values and practices like collective work and mutual assistance. This study concludes by proposing a framework that shows the interplay between the perception, knowledge, and attitudes that determine participation in PM. Additionally, its significance lies in the demonstration that PM is an effective tool to enhance farmers' decision-making as agricultural extension agents, thus promoting agrobiodiversity-based farming and innovation in FFS community. Future research can broaden the geographical scope, and deepen the understanding of the data analysis and use.